Characterization of the taste receptor‐related G‐protein, α‐gustducin, in pancreatic β‐cells. Issue 4 (27th February 2020) - Udagawa, Haruhide; Hiramoto, Masaki; Kawaguchi, Miho; Uebanso, Takashi; Ohara‐Imaizumi, Mica; Nammo, Takao; Nishimura, Wataru; Yasuda, Kazuki
Abstract: Aims/Introduction: Taste receptors, T1rs and T2rs, and the taste‐selective G‐protein, α‐gustducin, are expressed outside the taste‐sensing system, such as enteroendocrine L cells. Here, we examined whether α‐gustducin also affects nutrition sensing and insulin secretion by pancreatic β‐cells. Materials and Methods: The expression of α‐gustducin and taste receptors was evaluated in β‐cell lines, and in rat and mouse islets either by quantitative polymerase chain reaction or fluorescence immunostaining. The effects of α‐gustducin knockdown on insulin secretion and on cyclic adenosine monophosphate and intracellular Ca 2+ levels in rat INS‐1 cells were estimated. Sucralose (taste receptor agonist)‐induced insulin secretion was investigated in INS‐1 cells with α‐gustducin suppression and in islets from mouse disease models. Results: The expression of Tas1r3 and α‐gustducin was confirmed in β‐cell lines and pancreatic islets. Basal levels of cyclic adenosine monophosphate, intracellular calcium and insulin secretion were significantly enhanced with α‐gustducin knockdown in INS‐1 cells . The expression of α‐gustducin was decreased in high‐fat diet‐fed mice and in diabetic db / db mice. Sucralose‐induced insulin secretion was not attenuated in INS‐1 cells with α‐gustducin knockdown or in mouse islets with decreased expression of α‐gustducin. Conclusions: α‐Gustducin is involved in the regulation of cyclic adenosine monophosphate, intracellular calcium levels and insulin secretion in pancreatic β‐cells in a manner independent of taste receptor signaling. α‐Gustducin might play a novel role in β‐cell physiology and the development of type 2 diabetes. Abstract : The expression of α‐gustducin in pancreatic islets decreases with high‐fat diet feeding and obesity.